Kreativitas Generasi Pesona Indonesia (Genpi) Yogyakarta dalam Mempromosikan Destinasi Digital, Studi Kasus Pasar Ngingrong Gunungkidul - Budiman Mahmud Musthofa (Sekolah Vokasi, Universitas Gadjah Mada, 2019)
Abstract Generasi Pesona Indonesia (GenPI) is a community that was inaugurated by the Ministry of Tourism of the Republic of Indonesia in 2016 as an effort in the promotion and development of Indonesian tourism through a digital platform. GenPI is spread in various regions in Indonesia, one of which is in Jogjakarta. This study aims to find out the creativity of the GenPI Yogyakarta in promoting tourism destination, especially the Digital Destinations of “Pasar Ngingrong”, Gunungkidul, Yogyakarta. The method used in this study is a qualitative method with a case study. The results showed that creativity GenPI Jogja in promoting the Digital Destinations of “Pasar Ngingrong” was carried out using social media through the four stages of the promotion, which starts from the process of determining the content, content retrieval, content editing and uploading to social media. GenPI's promotional creativity has succeeded in increasing the number of tourists, helping to advance the digital destination of “Pasar Ngingrong” and providing various positive impacts for digital destination management, Government, and local communities. Keywords: GenPI, Promotion, Digital Destinations, Pasar Ngingrong